1995
DOI: 10.1093/carcin/16.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Cancer chemopreventive activity of brassinin, a phytoalexin from cabbage

Abstract: Brassinin [3-(S-methyldithiocarbamoyl)aminomethyl indole], a phytoalexin first identified as a constituent of cabbage, was synthesized and evaluated for cancer chemopreventive activity. Dose-dependent inhibition of 7,12-dimethylbenz[a]anthracene (DMBA)-induced preneoplastic lesion formation was observed with mouse mammary glands in organ culture, as was dose-dependent inhibition of DMBA-induced mouse skin tumors that were promoted by treatment with 12-O-tetradecanoylphorbol-13-acetate. Cyclobrassinin is a biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(86 citation statements)
references
References 20 publications
2
83
0
1
Order By: Relevance
“…QR is a phase II enzyme that detoxifies mutagenic carcinogens, and as an inducer of this enzyme, brassinin would be predicted to act as an 'anti-initiator'. However, the same study found that, in the two stage DMBA/TPA skin carcinogenesis model, brassinin acted instead as an 'anti-promoter' with no apparent impact on the initiation stage of carcinogenesis (Mehta et al, 1995). Unlike QR, IDO is likely to affect the promotional stage of carcinogenesis and, indeed, TPA is a powerful proinflammatory contact-sensitizer that would be expected to substantially elevate levels of IFNg, the principle cytokine inducer of IDO, in the draining lymph nodes (Thomson et al, 1993).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…QR is a phase II enzyme that detoxifies mutagenic carcinogens, and as an inducer of this enzyme, brassinin would be predicted to act as an 'anti-initiator'. However, the same study found that, in the two stage DMBA/TPA skin carcinogenesis model, brassinin acted instead as an 'anti-promoter' with no apparent impact on the initiation stage of carcinogenesis (Mehta et al, 1995). Unlike QR, IDO is likely to affect the promotional stage of carcinogenesis and, indeed, TPA is a powerful proinflammatory contact-sensitizer that would be expected to substantially elevate levels of IFNg, the principle cytokine inducer of IDO, in the draining lymph nodes (Thomson et al, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…While a variety of possible molecular mechanisms have been proposed to explain this activity, none has been directly validated in vivo. In particular, brassinin is cited as an inducer of quinone reductase (QR) based on data from a mouse mammary gland organ culture model in which incubation with 220 mM brassinin for 3 days resulted in a fourfold increase in QR activity (Mehta et al, 1995). QR is a phase II enzyme that detoxifies mutagenic carcinogens, and as an inducer of this enzyme, brassinin would be predicted to act as an 'anti-initiator'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In addition, brassinin (5b) has been reported to exhibit dose-dependent inhibition of DMBA-induced and TPA-promoted skin carcinogenesis. 19 Izutani et al demostrated that brassinin (5b) inhibits cell growth in human colon cancer cells by arresting the G1 phase via inceased expression of p21 and p27. 20 Spiroindoline phytoalexins and their derivatives exhibit an antiproliferative effect against human cancer cell lines.…”
Section: (±)-3a and Cis-(±)-3b With Cro3 12 Or A Mixture Of Diastereomentioning
confidence: 99%
“…20 Spiroindoline phytoalexins and their derivatives exhibit an antiproliferative effect against human cancer cell lines. 15,[21][22][23][24][25][26] Brassinin (5b) and its synthetic derivative 5-bromobrassinin (5c) act as bioavailable competitive inhibitors of indoleamine 2,3-dioxygenase (IDO), a tryptophan-catabolizing enzyme that promotes tumor escape via a mechanism of immune tolerance. 27,28 1-Methoxybrassinin (5a) displayed significant antiproliferative effect on intramolecular amastigotes of Trypanosoma cruzi and demonstrated a higher potency than shown by the currently used antichagasic agents (nifurtimox, benznidazol).…”
Section: (±)-3a and Cis-(±)-3b With Cro3 12 Or A Mixture Of Diastereomentioning
confidence: 99%